The management of penile intraepithelial neoplasia (PeIN): clinical and histological features and treatment of 345 patients and a review of the literature. (17th February 2022) - Kravvas, G.; Ge, L.; Ng, J.; Shim, T. N.; Doiron, P. R.; Watchorn, R.; Kentley, J.; Panou, E.; Dinneen, M.; Freeman, A.; Jameson, C.; Haider, A.; et al.
Abstract: Introduction: Penile intraepithelial neoplasia (PeIN) is a histological term for precancerous penile lesions. PeIN is important due to the high morbidity and mortality associated with progression to penile squamous cell carcinoma (PSSC). But PeIN is rare, contributing to a limited evidence-base for the relative efficacy of available treatment options. Objectives & methods: To consolidate and expand knowledge about PeIN and its treatment, we describe the clinical and histological characteristics, treatments and outcomes of 345 patients with PeIN, managed by our multidisciplinary team. Our results are compared and contrasted with those in the literature, following comprehensive review. Results: 8.7% of patients had concomitant, invasive PSCC, whilst 91.3% demonstrated PeIN alone. 84% had undifferentiated PeIN, and 10.7% differentiated PeIN (5.2%, not specified). Clinical or histological evidence of HPV alone was present in 58%; features of lichen sclerosus alone in 12%; features of both in 29.4%. Only 14.4% of patients could be treated solely with topical agents or cryotherapy, whereas the remaining 85.6% underwent some form of surgical intervention, circumcision being the mainstay. Just 2.6% progressed to PSCC. Conclusions: Clinical management of PeIN can be rationally optimized with excellent outcomes. Circumcision is important. Topical treatments alone are disappointing.